Reflective analysis on empirical theories in consciousness - Pae, Hongju (Frontiers in Psychology, 2025)
Contemporary theories of consciousness offer a range of explanatory perspectives. Global Workspace Theory emphasizes cognitive access, Higher-Order Theories focus on metacognitive representation, Integrated Information Theory centers on intrinsic experience, and Predictive Coding Theory models cognitive processes as probabilistic inference. While each theory provides valuable insights, they often remain in conflict due to differing assumptions about the nature of consciousness. This paper proposes a phenomenologically informed framework that clarifies the explanatory scope of each theory in relation to key features of lived experience. Rather than seeking to reduce consciousness to a single principle, I argue for a pluralistic approach that respects the distinctive contributions of each model. Through comparative analysis guided by phenomenological reflection and supported by recent interdisciplinary proposals, I show how these theories can be seen as addressing complementary dimensions of consciousness. The aim is not to construct a single unified theory, but to demonstrate how integration, grounded in reflective phenomenological analysis, can serve as a starting point toward a more adequate science of consciousness.